Synthesis and characterisation of microcrystalline cellulose-g-poly (Acrylamide) superporous absorbent composite using graft polymerisation methods - Suriati, Ghazali; Saidatul Shima, Jamari; Noor Liyana, Che Lah; Najahusna, Adnan (Elsevier Ltd, 2023)
Superabsorbent polymer was synthesised by using graft polymerisation method incorporated with micro crystalline cellulose (MCC) as a filler and sodium bicarbonate (NaHCO3) as the foaming agent. The addition of organic filler and porosity generator produced a highly porous biodegradable superabsorbent polymer composite (HP-PAM-g-MCC), which improved the characteristics of the acquired products, in comparison with the conventional SAP. Determination of water absorbency was tested by using the tea bag method after immersing in distilled water. The effects on amount of MCC and sodium bicarbonate addition towards water absorbency were studied to determine the optimum condition of PAM-g-MCC SAPs composite. The maximum water absorbency of PAM-g-MCC composite was achieved at 1.0 wt% of MCC and 1 wt% NaHCO3, resulting in 74.01 g/g and 93.96 g/g of water absorbency, respectively. The Fourier transform infrared (FTIR) and scanning electron microscope (SEM) analyses data revealed the presence of chemical bonding and morphological characteristics corresponding to the water absorption capacity of HP-PAM-g-MCC.